Um método analítico-comportamental para desenvolvimento de comportamentos empreendedores : processos de sistematização e avaliação dos efeitos - Marina Mendonça de Sousa (2023)
Entrepreneurship has garnered significant attention from researchers, public policy organizations, and the general population. Studies related to entrepreneurship or entrepreneurial education have presented compelling data and a consensus: the impacts generated by this activity are crucial for the economic and social development of any society. Generally, more developed countries have exhibited higher rates of entrepreneurial activities in terms of quantity and diversity when compared to less developed countries, highlighting the importance of providing more resources and support to the latter. Therefore, the main objective of this thesis was to systematize and evaluate a behavioral method that could enhance the development of behavioral aspects of entrepreneurs undergoing entrepreneurial education. This objective was achieved through three studies. The systematic review conducted in this study demonstrated that the investigated entrepreneurial education programs exhibited heterogeneity in nearly all their components, such as the content offered, duration, format of meetings, among others. Among the identified objectives, those related to increasing entrepreneurial intention, enhancing entrepreneurial skills and competences, expanding specific knowledge, fostering new ventures, and facilitating the growth of existing companies stood out. However, there was a lack of interventions specifically aimed at developing behavioral aspects. Similarly, the second study of this thesis sought to systematize a method that could provide behavioral interventions targeting specific objectives identified within the behavioral framework of entrepreneurship. To accomplish this, a database was utilized, which included interventions carried out in entrepreneurial education programs provided by a specialized consulting company. Based on these data, three stages were conducted. The first stage sought validation that the guiding psychological framework for behavioral interventions was the Experimental Analysis of Behavior. The second stage characterized the behavioral aspects and intervention formats of the programs. The third step involved the systematization of the method known as the Troposlab Analytical-Behavioral Method (MACT). As a result of these three stages, 39 intervention items were derived and divided into four categories (challenges, tasks, objectives, and behavioral outcomes), along with suggestions regarding the target audience, duration, number of meetings, tools, and mentor training. Subsequently, the third study aimed to investigate the behavioral effects of such a method on intrapreneurs working in entrepreneurial education contexts. The target audience comprised employees of a Hospital Foundation involved in initial-phase internal entrepreneurship projects. The research design employed was quasi-experimental, with 35 participants divided into 9 groups of three or four individuals. The outcome measures included entrepreneurial potential (Entrepreneurial Potential Scale), intention to undertake (Entrepreneurial Intention Scale), psychological flexibility (AAQ-II), and resilience (BRS-BR). A socio-demographic questionnaire was used to characterize the sample, along with a questionnaire to assess the participants' experience with the program. The results indicated statistically significant mean differences between the pre- and post-intervention moments for six of the evaluated outcomes, namely: intention to undertake, opportunity, planning, goals, total entrepreneurial potential, and psychological flexibility. Furthermore, most of the categories defined by the experience satisfaction questionnaire elicited "satisfied" or "very satisfied" responses. Thus, based on the obtained results, it can be concluded that the construction and/or systematization of interventions that directly train skills appear to yield significant results in acquiring these skills and should be considered as compelling alternatives. Furthermore, other studies and methods can be developed with the aim of directly training behavioral aspects. Finally, this work contributes to the scientific production in the field of entrepreneurship, and its results shed light on the importance of systematically developing behavioral aspects within the processes of entrepreneurial education.